Pengaruh Kebijakan Dividen, Likuiditas, Dan Profitabilitas Terhadap Nilai Perusahaan Dengan Good Corporate Governance Sebagai Variabel Moderasi Pada Perusahaan Food and Beverage Yang Terdaftar Di Bei Periode 2017-2022 - Yundila Suswiantini; I Nengah Arsana; Baiq Desthania Prathama (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2025)
This study aims to examine the effect of Dividend Policy, Liquidity, and Profitability on Company Value with Good Corporate Governance as a moderating variable in Food and Beverage companies listed on the IDX for the 2017-2022 period. This type of research is quantitative research with a causal associative approach. The samples used in this study were 7 companies with 42 observation data. The data collection method used was purposive sampling. Data analysis technique using multiple linear regression analysis. The results of this study indicate that the Dividend Policy has the effect of has a positive and insignificant effect on firm value with a tcount > ttable (0.283 > 0.05), Liquidity has a negative and significant effect on firm value with a tcount <ttable (0.003<0.05), Profitability has a negative and insignificant effect on firm value with tcount > ttable (0.098 > 0.05). Dividend Policy, Liquidity, and Profitability have a simultaneous effect on firm value. Good Corporate Governance is able to moderate (strengthen) liquidity on firm value, while Good Corporate Governance is unable to moderate (weaken) the effect of dividend policy and profitability on firm value.